The self-assessment system and its compliance costs / Muzainah Mansor, Natrah Saad and Idawati Ibrahim - Mansor, Muzainah; Saad, Natrah; Ibrahim, Idawati (Faculty of Accountancy, 2004)
The self-assessment system has been implemented on companies since 2001 as to replace the former official assessment system. As such, procedural issues and compliance cost associated with the new assessment system are of significant interest to the taxpayers. This study was conducted in the year 2002 i.e. after one year the self-assessment system for companies has been put into practice. It focuses on the compliance cost in terms of the time spent by the taxpayers. In the study, time spent is used to measure the increment of compliance cost since time devoted to compliance activities is very much associated with the cost incurred. The respondents in this study are the small and medium enterprises (SMEs) and the tax agents in the northern region i.e. Perlis, Kedah and Penang. As this is an exploratory study, the researchers used convenience sampling, which enabled them to get fifty-six SMEs and forty-five tax agents in the stated area. From the survey on the SMEs, the findings reflected that the most prominent variable is the time spent for discussion with tax agents (78.83 percent), which represented the major source of increment in compliance cost under the new system, followed by learning the new tax laws (55.40 percent); paying taxes (50.00 percent); record-keeping (48.20 percent); and answering IRB queries (44.70 percent). Meanwhile, 90.00 percent of the tax agents suggested that there was an increase in time spent under the new system for the total hours spent in complying with the new system, learning the new tax laws, preparing tax returns, and discussion with clients. Only 63.70 percent of them implied that there was an increase in time spent in answering IRB queries.